Вопросы развития языка в трудах представителей разных поколений Казанской лингвистической школы - Абдулхакова, Ляйсэн (Studia Rossica Posnaniensia, 2014)
The article discusses some of the papers which were written by the representatives of the Kazan linguistic school, founded by I.A. Baudouin de Courtenay, and which are dedicated to the development of language. It also highlights the main directions in the studies carried out by Kazan’s modern scholars who use these ideas and represent the historical-linguistic trend that was established by V.M. Markov.